Theory of mind in students with mild and moderate intellectual disability - Petrushevska, Mirjana; Chichevska Jovanova, Natasha (Faculty of Philosophy, Skopje, 2014)
The subject of this research is the adoption of the theory of mind among students with mild and moderate intellectual disabilities. This research was conducted on a sample of 197 respondents: 62 pupils with typical development, between 3 and 6 years old and 93 pupils with mild and moderate intellectual disabilities between 7 and 16 years. A total of 42 teachers and special educators took part in this research. Three test-stories and one questionnaire for both, teachers and special educators were used in the research. By this research data about the adoption level of the theory of mind among the individuals with special needs as well as conclusions about the attitudes and opinions of the teachers in elementary schools and of the special educators from the special schools for children with special needs. As more important we emphasize: the theory of mind of individuals with mild and moderate intellectual disability is not developing in accordance with the age and mental age, that is the theory of mind is failing to develop by the age of sixteen during the educational process. Individuals with moderate intellectual disability are not capable to understand their own mental conditions, emotions, wishes, believes and intentions of other people. Performance of tasks of the theory of mind does not improve with the growth of verbal and mental years compared with children with typical development of same mental and calendar age. The adoption of the theory of mind in individuals with special needs is not in line with the growth of mental and verbal age as is the case in individuals with typical development.
Теорија на умот кај учениците со лесна и умерена интелектуална попреченост
Keywords: theory of mind, mild intellectual disabilities, moderate intellectual disabilities